FORMULASI DAN UJI AKTIVITAS KRIM TABIR SURYA EKSTRAK BIJI KAKAO (Theobroma cacao L.) DENGAN KOMBINASI AVOBENZONE DAN OCTYL METHOXYCINNAMATE - Dian Ika Perbina Meliala; Wahyudi Wahyudi; Nelva Nelva (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
Sunscreen is a cosmetic ingredient that can physically resist UV A and UV B rays. UV A radiation can cause brown color on the skin and UV B rays can cause skin burn. Although the skin has protection against sunlight, it is still necessary to use sunscreen on the skin. Substances Antioxidants are substances that at small concentrations can significantly inhibit oxidation on the substrate caused by free radicals. One plant that contains natural antioxidants is cocoa beans.To determine the value of Sun Protection Factor (SPF) from cocoa bean extract formulated in cream form and in combination with Avobenxone and Octyl Methoxycinnamate (OMC). Making cocoa bean extract was extracted by maceration using 80% ethanol solvent, making sunscreen extract of cocoa bean extract made in three formulations with concentrations of 10%, 15% and 20%, evaluating cream preparations and determining SPF values (Sun Protection Factor). using UV-Vis spectrophotometry.The results of the study showed differences in SPF values between cocoa bean extract creams. The concentration that has the highest SPF value is 20% with an SPF value of 15.22. The SPF value obtained from each formula is in the maximum category, the recommended value is 15.00. The best SPF value is found at a concentration of 20%, which is 15.22.